Pengembangan E-Modul Interaktif Berbantuan Flipbook pada Materi Daerahku dan Kekayaan Alamnya untuk Meningkatkan Hasil Belajar Kelas IV - Siti Zulaikha; Elly Sukmanasa; Desti Herawati (Mataram University, 2026)
The increasing integration of digital technology in education demands teaching materials that are interactive and responsive to students' learning needs, yet many primary schools still rely on printed textbooks that limit student engagement. This study aims to develop an interactive e-module assisted by Flipbook covering the topic